Ischemic post-conditioning in acute ischemic stroke thrombectomy: A phase-I duration escalation study - Wu, Longfei; Zhang, Bohao; Zhao, Wenbo; Ji, Xunming; Wei, Ming (Frontiers in Neuroscience, 2022)
Background Previous experimental studies have found that ischemic post-conditioning exhibits neuroprotective effects by alleviating ischemia-reperfusion injury in an acute ischemic stroke model, and its efficacy is thought to be related to the duration of ischemic post-conditioning. However, ischemic post-conditioning has not been used in patients with acute ischemic stroke. This study aims to determine the safety, tolerability, and maximum tolerable duration of ischemic post-conditioning in patients with acute ischemic stroke receiving mechanical thrombectomy. Methods Patients with acute ischemic stroke with unilateral middle cerebral artery M1 segment occlusion eligible for mechanical thrombectomy will be enrolled. We adopt a 3 + 3 dose-escalation design with a duration escalation schedule of 0, 1, 2, 3, 4, and 5 min × 4 cycles for the ischemic post-conditioning study. After successful reperfusion following mechanical thrombectomy, the balloon for ischemic post-conditioning will be inflated at the site proximal to the culprit lesion four times for 0–5 min with low-pressure (3–4 atmospheres) inflations, each separated by 0–5 min of reflow. We pre-defined the major responses (vessel perforation or rupture, reocclusion of the culprit vessel after ischemic post-conditioning, vessel dissection, severe vasospasm, ischemic post-conditioning related thrombotic events, and rupture of the balloon used for ischemic post-conditioning) as the stopping rules. Each patient will undergo a rigorous evaluation to determine the safety, tolerability, and maximum tolerable duration of ischemic post-conditioning. Discussion This will be the first clinical study to ascertain the safety and tolerability of ischemic post-conditioning in patients with acute ischemic stroke receiving mechanical thrombectomy. The maximum tolerable duration obtained in this study will also serve as a starting point for future studies on the efficacy of ischemic post-conditioning. Clinical trial registration [https://clinicaltrials.gov], identifier [NCT05153655].